2009
DOI: 10.1086/605379
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Variation in Maternal Yolk Hormone Transfer in a Wild Bird Population

Abstract: Differential reproductive investment by the mother can critically influence offspring development and phenotype, and strong selection is therefore expected to act on such maternal effects. Although a genetic basis is a prerequisite for phenotypic traits to respond to selection and thus to evolve, we still know very little about the extent of heritable variation in maternal effects in natural populations. Here, we present the first estimates of intrafemale repeatability across breeding seasons and estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 80 publications
(87 reference statements)
2
65
0
Order By: Relevance
“…We found moderate heritability for yolk T concentration, which is consistent with previous studies showing significant heritability for T from lines selected for yolk T in captive quails (h 2 = 0.42; Okuliarova et al, 2011) and mother-daughter correlations from wild collared flycatchers (h 2 = 0.75; Tschirren et al, 2009). Furthermore, in contrast to studies in the wild collared flycatcher, where yolk A4 concentration was not heritable (Tschirren et al, 2009), but consistent with the study in quails (Okuliarova et al, 2011), we found moderate heritability also for yolk A4 concentration. Similarly to our study, also in captive great tit lines selected for personality, co-selection for both yolk T and A4 concentrations was confirmed .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found moderate heritability for yolk T concentration, which is consistent with previous studies showing significant heritability for T from lines selected for yolk T in captive quails (h 2 = 0.42; Okuliarova et al, 2011) and mother-daughter correlations from wild collared flycatchers (h 2 = 0.75; Tschirren et al, 2009). Furthermore, in contrast to studies in the wild collared flycatcher, where yolk A4 concentration was not heritable (Tschirren et al, 2009), but consistent with the study in quails (Okuliarova et al, 2011), we found moderate heritability also for yolk A4 concentration. Similarly to our study, also in captive great tit lines selected for personality, co-selection for both yolk T and A4 concentrations was confirmed .…”
Section: Discussionsupporting
confidence: 91%
“…However, the effect of captive conditions may alter (increase or decrease) the phenotypic variation, which may then affect the size of the heritability estimate. Finally, we should mention that our sample size is not very large in respect to traditional quantitative genetic analyses; however, similar sample sizes did show significant heritabilities in a previous study on yolk testosterone (52 mother-daughter pairs, Tschirren et al, 2009).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In experiments manipulating the prebreeding diet, however, it has been shown that highcondition females do not lay eggs with higher yolk androgen concentrations than low-condition females do [6,7]. Similarly to experimental results, correlative data have also shown that high-condition females deposit a lower or equal (but not greater) concentration of androgen in their egg yolks compared with low-condition females [5,8]. However, female mass was measured only once (at any time before, during or even after egg formation) in these studies, which therefore did not test for the energetic cost of yolk androgen deposition, in terms of body mass change.…”
Section: Introductionmentioning
confidence: 76%
“…it acts as a mediator of maternal effects [14][15][16]), and the costs and benefits of T exposure during prenatal development appear to depend on the social and environmental conditions encountered by the offspring [17][18][19]. Yolk T transfer is known to be heritable [20][21][22], but the design of previous studies did not allow detection of potential sex-linkage. We predict that if yolk T transfer is inherited along the maternal line, females will resemble their maternal, but not their paternal grandmother in their transfer of T to the eggs.…”
Section: Introductionmentioning
confidence: 99%